An Analysis on Bengali handwritten conjunct character recognition and prediction - Munawar, Maazin; Roy, Yagghaseni Saha; Hussain, Mohammed Mudabbir (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.